A drug utilization study in glaucoma patients in ophthalmology out patient department in a tertiary care hospital - Patel, Kaushal B.; Dumra, Gurusharan H.; Singh, Adarsh Jeet; Vyas, Abhishek; Parmar, Chetan G. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: According to World Health Organization (WHO) studies Glaucoma is a chronic progressive symptomatic disease that damages retinal cells and is one of the leading cause of preventable blindness worldwide. Availability of newer topical agents has modernized the management of glaucoma. Methods: A prospective observational study was carried out from August 2016 to December 2016 at ophthalmology Out Patient Department of L.G General Hospital, Ahmedabad by authours after the approval of the Institutional Ethics Committee. Results: Out of total 101 patients, 71 were males and 30 were females. Average age of patient is 54 years. Common variant of Glaucoma was Primary Open Angle Glaucoma in 57.4% of patients. Average number of drugs per prescription was 2 (45%). Most commonly used Fixed Dose Combination was Brimonidine +Timolol Drops which was used in 87 (86.1%) patients. Most commonly used adjuvant drug was Tab. Acetazolamide (60% of patients). Conclusions: Common variant of Glaucoma was Primary Open Angle Glaucoma in 57.4% of patients. Most commonly used Fixed Dose Combination was Brimonidine+Timolol Drops which was used in 87 (86.1%) patients and commonly used Single drug therapy is Tab. Acetazolamide in (60% of patients).